Shock electroconvulsive therapy - McFarlin, Brian; Osborne, Brad.; Sabat, Christopher; Vilim, Brian; AMS Production Group, Inc.; Concept Media, inc. (Irvine, CA : Concept Media, 2007)
This series reveals the personal stories of a dozen people who underwent electroconvulsive therapy for the treatment of severe depression or bipolar disorder., It features candid, intimate interviews with patients and healthcare professionals who discuss their experiences with this treament modality which has been both derided as barbaric and praised as miraculous. Included in this series is an historical perspective of ECT, including information about well-know artists such as Ernest Hemingway and Cole Porter who underwent this treatment many years ago as well as the influence of motion pictures in their less-than-accurate depitions of the procedure. Shock concludes with a discussion of how the effects of ECT on the brain's physiology may make it a successful treatment modality for depression as well as a real-time demonstration of ECT administered to a patient.
Fakulti Perubatan Veterinar.
Director of photography, Brian Vilim ; cinematographer, Brian McFarlin ; original music composed by Brad Osborne.
Narrated by Christopher Sabat.
Keywords: Electroconvulsive therapy; Electroconvulsive Therapy; Shock therapy